Effect mechanism of SO2 on Hg0 adsorption over CuMn2O4 sorbent. (1st December 2022) - Xiao, Yiyang; Yang, Yingju; Liu, Jing; Zhang, Aijia
Highlights: Effect mechanism of SO2 on Hg removal by CuMn2 O4 was studied by experiment and DFT. The high-temperature inhibitory effect of SO2 is related to the sorbent sulfation. SO2 chemisorption of CuMn2 O4 sorbent is attributed to the orbital hybridization. SO2 presence increased the activation energy barrier of Hg*-to-HgO conversion. Abstract: SO2 is an important acid flue gas component during solid fuel combustion. The effects of SO2 on the Hg 0 removal performance of CuMn2 O4 sorbent and its reaction mechanism were investigated by conducting the mercury adsorption experiments and theoretical calculations. The results showed that SO2 concentration coupling with the high temperature was the predominant factor affecting the Hg 0 removal performance of CuMn2 O4 sorbent. At a relatively high temperature (≥200 °C), the presence of SO2 significantly inhibited Hg 0 removal by CuMn2 O4 sorbent, and the inhibitory effect was significantly enhanced with the increase of temperature. Hg 0 removal efficiency decreased from 88.2 % at 200 ℃ to 17.98 % at 350 °C due to the SO2 sulfation of sorbent surface. Hg 0 removal performance of CuMn2 O4 sorbent was not sensitive to the variation of SO2 concentration at the low temperature of 150 °C. DFT calculation results showed that SO2 is chemically adsorbed on the sorbent surface, and the adsorption energy of the most stable configuration is −111.78 kJ/mol. The chemisorption of SO2 on the sorbent surface is attributed to the orbital hybridization among Cu, Mn and O atoms. The adsorption energy of Hg 0 on the CuMn2 O4 surface decreased in the presence of SO2 . The transformation pathway of Hg 0 in the presence of SO2 includes three steps: Hg 0 adsorption, O2 adsorption, and Hg*-to-HgO conversion. The presence of SO2 increased the activation energy barrier of Hg* oxidation into HgO.